The Korean vegan cookbook : reflections and recipes from Omma's kitchen - Lee Molinaro, Joanne (Avery, Penguin Random House LLC, 2021)
"Korean dishes, some traditional and some reimagined, from the home cook and storyteller behind @thekoreanvegan on TikTok"--